1983
DOI: 10.1007/bf01295812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 16, 16-dimethyl prostaglandin E2 on alkaline secretion in isolated canine gastric mucosa

Abstract: An isolated fundic mucosal preparation of dog stomach which is capable of exhibiting an alkaline secretion is described. A stable secretion was established 40 min to 1 hr after the mucosa was pretreated with the H2-antagonist cimetidine to block spontaneous acid output. Alkaline secretion decreased when Ca2+ was removed from the nutrient solution. This secretion was stimulated by dibutyryl cyclic GMP, but was not altered by acetylcholine, carbachol, or 16,16-dimethyl PGE2. Alkaline secretion from a similar ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies in vivo have shown that prostaglandins stimulate non-parietal secretion from mammalian stomach (rat: Bolton, Palmer & Cohen, 1978; dog: cat: Gascoigne & Hirst, 1981), and that this secretion consists principally of Na+ and Clions with smaller amounts of K+ and HC03-(dog: Miller, Henagan, Watkins & Loy, 1983;cat: Smeaton & Hirst, 1984;rat: Bunce, 1985). Studies on non-parietal secretion in mammalian isolated tissues have shown that 16,16-dimethyl-prostaglandin E2 stimulates bicarbonate secretion in rabbit gastric mucosa (Rees, Gibbons & Turnberg, 1983), although no such secretion was observed in dog gastric mucosa (Kuo, Miller & Shanbour, 1983). In contrast, in the latter tissue, Chaudhury & Jacobson (1978) found that 16,16-dimethyl-prostaglandin E2, rather than stimulating secretion, increased the rate of net sodium absorption across the mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vivo have shown that prostaglandins stimulate non-parietal secretion from mammalian stomach (rat: Bolton, Palmer & Cohen, 1978; dog: cat: Gascoigne & Hirst, 1981), and that this secretion consists principally of Na+ and Clions with smaller amounts of K+ and HC03-(dog: Miller, Henagan, Watkins & Loy, 1983;cat: Smeaton & Hirst, 1984;rat: Bunce, 1985). Studies on non-parietal secretion in mammalian isolated tissues have shown that 16,16-dimethyl-prostaglandin E2 stimulates bicarbonate secretion in rabbit gastric mucosa (Rees, Gibbons & Turnberg, 1983), although no such secretion was observed in dog gastric mucosa (Kuo, Miller & Shanbour, 1983). In contrast, in the latter tissue, Chaudhury & Jacobson (1978) found that 16,16-dimethyl-prostaglandin E2, rather than stimulating secretion, increased the rate of net sodium absorption across the mucosa.…”
Section: Introductionmentioning
confidence: 99%